Enzyme Kinetics and High-Throughput Screening for Biocatalysis and Diagnostics - C. Engel, Paul; Narayanan, Rajesh (Current Biotechnology, 2015)
The numerical imperative of random mutagenesis and high-throughput screening has created an overwhelming pressure for single measurements of enzyme activity as a preliminary diagnostic of functional improvement even if this leads on to a more traditionally thorough kinetic analysis of each potentially interesting mutant. This paper argues, with examples, that it is therefore all the more important to apply kinetic thinking to the initial choice of conditions for the screening reaction and as far as possible match those conditions to those of the intended application. Without such planning there is a real risk of missing valuable mutants and of wasting time on many that do not fit the requirement. Key issues are choice of substrate concentration and direction of reaction and awareness of rate limiting steps in the mechanism.
Keywords: enzyme improvement